LEVEL OF ANXIETY AMONG THE COUPLES OF ARRANGE MARRIED AND LOVE MARRIED (International Journal of Food and Nutritional Sciences, 2022)
Research Background: Anxiety, the common thread that connects the various types of anxiety disorders, can be experienced in different ways, from the intense fear associated with a panic attack to the generalized sense of foreboding or worry in generalized anxiety disorder. In this study, an investigator has focused on finding out the level of anxiety among the couples of arrange married and love married. Objectives: The study objective was, to study the significance difference in level of anxiety among the couples of arrange married and love married. Another, objective was, to study the significant difference in level of anxiety among the male and female. Procedure: For the study one hundred twenty marital adults were selected from male and female. Their age range was between 30 to 50 years. The study type of couples and type of gender were independent variables and level of anxiety was dependent variable. The study purposive sampling technique was used for the selection of the samples. In the present study, samples were selected from various urban and rural locations in the state of Maharashtra. This study anxiety scale developed by Dr. R. L. Bhardwaj, Dr. H. Sharma, and Dr. M. Bhargava has been used.Conclusions: It is concluded that, the arrange married and love married couples have found equal on their level of anxiety. The male and female adults have found equal level on their level of anxiety. There is insignificant interaction found between the effects of type of couples and type of gender. Application: This study will definitely help us to understand the significant difference between arrange married couples and love married couples in terms of their level of anxiety. This study will help us to understand the significant difference between married males and married females in terms of their level of anxiety.